2020
DOI: 10.1021/acs.jpclett.0c00385
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Shallow/Deep Trap States beyond the Conduction Band Minimum in Defect-Tolerant CsPbBr3 Perovskite Quantum Dot: Control over the Degree of Charge Carrier Recombination

Abstract: Perovskite quantum dots (PQDs) are known to be defect-tolerant, possessing a clean band gap with optically inactive benign defect states. However, we show that there exist significant deep trap states beyond the conduction band minimum, although the extent of shallow trap states is observed to be minimal. The extent of deep trap states beyond the conduction band minimum seems to be significant in PQDs; however, the extent is less than that of even optically robust CdSe-and InP-based core/alloy-shell QDs. In-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…While at room temperature the efficient detrapping process slows down the PL decay, the emission from these localized states becomes significant at low temperatures as evident in the formation of the additional low-energy PL peak (Figure e) . Very recently, trapping of the hot charge carriers in states within the band itself has been reported for APbBr 3 NCs. ,, …”
Section: Optical Propertiesmentioning
confidence: 82%
“…While at room temperature the efficient detrapping process slows down the PL decay, the emission from these localized states becomes significant at low temperatures as evident in the formation of the additional low-energy PL peak (Figure e) . Very recently, trapping of the hot charge carriers in states within the band itself has been reported for APbBr 3 NCs. ,, …”
Section: Optical Propertiesmentioning
confidence: 82%
“…Assuming that the RP-PNCs possess a higher density of such states due to the aforementioned loss of stabilizing ligands, the higher binding energies in RP films prevent the excitons from dissociation and therefore result in stronger UC-PL. It is likely that the blue shift occurs when the excited electrons recombine from the states above the conduction minimum band . However, since the blue shift in UC-PL spectra is specific to RP-films only, it would be reasonable to attribute it to the presence of RPs, precisely to the expansion of the band gap due to the band offset across the RP boundary by ∼327 meV .…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is likely that the blue shift occurs when the excited electrons recombine from the states above the conduction minimum band. 34 However, since the blue shift in UC-PL spectra is specific to RP-films only, it would be reasonable to attribute it to the presence of RPs, precisely to the expansion of the band gap due to the band offset across the RP boundary by ∼327 meV. 18 The origin of the red and blue shifts seen in the UC-PL is schematically illustrated in Figure S5.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[48,53] Using the same techniques of single-molecule spectroscopy and time-resolved spectroscopy, the fluorescence blinking has recently been investigated in MAPbBr 3 QDs, [57][58][59][60] CsPbBr 3 QDs, [61][62][63][64] 0D Cs 4 PbBr 6 , [65] MAPbI 3 QDs. [66] Mandal et al [67] observed blinking in inorganic perovskite CsPbBr 3 QDs. As shown in Figure 2A,B, different ON/OFF power laws are confirmed for different excitation wavelengths of 405, 463, and 488 nm.…”
Section: Fluorescence Intermittency In Single Perovskite Quantum Dot mentioning
confidence: 99%
“…Reproduced with permission. [ 67 ] Copyright 2020, American Chemical Society. C) Scheme for different recombination processes in a single CsPbBr 3 nanocrystal.…”
Section: Mobile Ion‐induced Fluorescence Blinkingmentioning
confidence: 99%